NCCT Head Findings in Patients of Chronic Renal Failure with Altered Sensorium: A Prospective Study in a Tertiary Care Centre - Kumar, Vinod; Singh, Achint; Bhagat, Ritu; Azad, Ahmar Javid (Highlights on Medicine and Medical Science Vol. 3, 2021)
Introduction: The central nervous system (CNS) is commonly impacted in uremics and has been studied in these individuals in many ways. Various theories about the origin of central nervous system tract lesions in chronic renal failure have been proposed from time to time. In the majority of studies, urea has been implicated. Hemodialysis patients are at high risk of cognitive impairment due to their older age and high prevalence of stroke and cardiovascular risk factors. Aim: The goal is to investigate the NCCT Head findings in chronic renal failure patients. Materials and Methods: This is a one-year prospective study undertaken at GMC, Jammu, a tertiary care centre, from November 2016 to October 2017. In our study, 64 patients were included, 36 of whom were males (56.25 %) and 28 of whom were females (43.75%). Patients ranged in age from 18 to 60 years old. Results: Out of 64 patients undertaken in our study, 8 patients (12.5%) had ischaemic stroke, 6 patients (9.37%) had haemorrhagic stroke while 2 patients (3.12%) had both the lesions. Conclusion: In patients with chronic renal failure, neurologic symptoms have been documented frequently. CKD patients suffer from moderate to severe chronic cognitive impairment, which goes undiagnosed in the majority of cases.